Public-private partnership: problems of contractual settlement - Kolomoiets, Tetiana; Alimov, Kyrylo; Matiiko, Mykola; Popeliuk, Vadym; Huk, Iryna-Mariia (Amazonia Investiga, 2022)
Given the benefits of public-private partnership (PPP), PPP relations, as well as the problems that arise in the contractual settlement of such relations are becoming increasingly important. Legislative requirements for the contractual form of partnership and an open list of contracts that can be concluded within the PPP do not differ in their clarity and clarity of interpretation, which results in the ambiguity of views on the rule of law when concluding agreements. Therefore, it is essential to analyze the problematic aspects of contractual regulation of relations in the field of PPP and suggest ways to solve them. The work aims to study the problems of contractual settlement of PPP. Research methodology such methods as the dialectical method, analysis and synthesis, induction and deduction, proof and refutation, comparison, generalization. As a result of the study, the problematic aspects of concluding agreements in the field of PPP were analyzed. In particular, it was concluded that today, despite the legal basis for the implementation of PPP, the implementation of such projects has some problems that are manifested in both legal and organizational areas. One of the problems is the greater role of the state partner in the implementation of PPP projects, which is manifested in the expanded scope of rights compared to the private partner (ownership of facilities created in the implementation of PPP projects), and, accordingly, lack of business interest in participation in projects not on mutually beneficial terms.